A cinematic view on North Korean spies from the south in Secretly Greatly (2013) - Kim, Ji-Eun (2017)
Access online through this link: https://www.plarideljournal.org/article/cinematic-view-north-korean-spies-south-secretly-greatly-2013
Keywords: Film reviewing; Motion pictures -- South Korea; North Korea